Women's Workwear Design Inspired by Minangkabau Traditional Culture - Setiawardhana, Dedy Rachmad; Meiliana, Sinta (International Journal of Engineering, Science and Information Technology, 2025)
Women's workwear designed specifically for the work environment or professional reflects professionalism, politeness, and comfort during work. The definition of women's workwear can vary depending on company policies, business norms, and the level of formality in the workplace. In this context, this study explores the design of women's workwear that combines elements of Minangkabau culture, such as motifs and colors, to create unique and highly artistic works. This study is also inspired by the position of Minangkabau women who are central figures and depict wise women, researchers combine this decorative motif in one workwear. The process of combining designs on motifs, patterns, and materials on the sewing of workwear is a creative step in creating an authentic impression. Case studies on traditional Minangkabau decorative motifs are significant elements in the study, emphasizing the role of cultural preservation and the important role of women in Minangkabau culture. This research not only covers efforts to preserve and introduce Minangkabau culture, but also seeks innovation in workwear design. This innovation reflects the adaptation of traditional workwear to be more modern, but still strengthens the cultural context. Workwear design involves the creative and innovative role of professional tailors, which socially and culturally can create a positive impact on society. The public's response to the use of workwear that combines decorative elements and innovation is an important part of understanding the design of Minangkabau women's workwear that reflects cultural richness.